Heat‐related illness in Washington State agriculture and forestry sectors. Issue 8 (20th June 2014) - Spector, June T.; Krenz, Jennifer; Rauser, Edmund; Bonauto, David K.
<x xml:space="preserve">Abstract</x> Background We sought to describe heat‐related illness (HRI) in agriculture and forestry workers in Washington State. Methods Demographic and clinical Washington State Fund workers' compensation agriculture and forestry HRI claims data (1995–2009) and Washington Agriculture Heat Rule citations (2009–2012) were accessed and described. Maximum daily temperature (Tmax) and Heat Index (HImax) were estimated by claim date and location using AgWeatherNet's weather station network. Results There were 84 Washington State Fund agriculture and forestry HRI claims and 60 Heat Rule citations during the study period. HRI claims and citations were most common in crop production and support subsectors. The mean Tmax (HImax) was 95°F (99°F) for outdoor HRI claims. Potential HRI risk factors and HRI‐related injuries were documented for some claims. Conclusions Agriculture and forestry HRI cases are characterized by potential work‐related, environmental, and personal risk factors. Further work is needed to elucidate the relationship between heat exposure and occupational injuries. Am. J. Ind. Med. 57:881–895, 2014. © 2014 Wiley Periodicals, Inc.